Results of Czech gymnasium students in the TIMSS Advanced 1995 specialized physics test repeated in 2023 - Pschotnerová, Petra; Mandíková, Dana; Chvál, Martin (Scientia in educatione, 2024)
The paper presents the first results of the TIMSS Advanced 1995 specialized physics test re-administered to final-year students of gymnasiums in the Czech Republic in 2023. In 2023, we used the original test booklets from 1995 in paper form. Of 90 gymnasiums from 1995, 72 participated in the repeated survey. Another 10 gymnasiums participated as replacement schools. In 1995, 819 students participated in the physics test. In the paper, we work with a sample of 1602 students from 2023. The overall mean achievement of students has decreased significantly compared to 1995. Males worsened more than females. Student mean achievement significantly lowered in all five physics content areas. The largest decrease in mean was observed in items from mechanics. More than a 10% decrease in the mean achievement most often appeared in items from the area of modern physics. In the case of open-ended items to which students had to create their own answers, the decrease in mean achievement was mainly due to the fact that students did not solve them at all. This may be due to the lower knowledge of the students caused by the reduction in the number of lessons devoted to teaching physics, but also to the lower motivation of the students when solving the test.